Evolutionary links between telomeres and transposable elements. - Pardue, M.L.; Danilevskaya, O.N.; Traverse, K.L.; Lowenhaupt, K. (Genetica, 1997)
Transposable elements are abundant in the genomes of higher organisms but are usually thought to affect cells only incidentally, by transposing in or near a gene and influencing its expression. Telomeres of Drosophila chromosomes are maintained by two non-LTR retrotransposons, HeT-A and TART. These are the first transposable elements with identified roles in chromosome structure. We suggest that these elements may be evolutionarily related to telomerase; in both cases an enzyme extends the end of a chromosome by adding DNA copied from an RNA template. The evolution of transposable elements from chromosomal replication mechanisms may have occurred multiple times, although in other organisms the new products have not replaced the endogenous telomerase, as they have in Drosophila. This is somewhat reminiscent of the oncogenes that have arisen from cellular genes. Perhaps the viruses that carry oncogenes have also arisen from cellular genetic systems.